Comparative Analysis of the Implementation of the Malcolm BaldrigeCriteria for Performance Excellence (MBCfPE) on Healthcare ServicePerformance at Community Health Centers (Puskesmas): A Study ofCOVID-19, Tuberculosis, and HIV Program - Edi Suhartono (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Analysis of the Implementation of the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) on Healthcare Service Performance at Community Health Centers (Puskesmas) Objective : 1. analyzed COVID-19 management at Dumai City Health Centers using a quantitative cross-sectional design involving 129 respondents 2. assessed the performance of Licin Public Health Center, Banyuwangi, in TB control using the MBCfPE framework 3. examined the achievement of Minimum Service Standards (SPM) for healthcare services among populations at risk of HIV in Depok City Health Centers using a cross-sectional design across 38 centers Research Methods/ Implementation Methods : Malcolm Baldrige Results : From the results of all journals taken using the Malcolm Balgride method, very good results were shown. Overall, these studies demonstrate that the Malcolm Baldrige framework is an effective tool for evaluating and improving healthcare service performance, particularly in leadership, strategic planning, and customer focus dimensions. Continuous implementation of Baldrige principles is essential for achieving excellence and sustainability in public health service delivery.